The fingerprints of dioxin-like bromocarbazoles and chlorocarbazoles in selected forest soils in Germany. (November 2016) - Mumbo, John; Pandelova, Marchela; Mertes, Florian; Henkelmann, Bernhard; Bussian, Bernd M.; Schramm, Karl-Werner
Abstract: The occurrence of bromocarbazoles and chlorocarbazoles was studied in 86 forest soil samples from different regions in Germany. Carbazole, 3-chlorocarbazole, 3-bromocarbazole and 3, 6-dibromocarbazole were qualitatively detected in the humic layer of 59 soil samples with bromocarbazoles reported here for the first time in soil. Furthermore, the halogenated carbazoles, PCDD/Fs and PCBs were detected in the humic and mineral soil horizons (0–5 cm and 5–10 cm) of a subset of 11 soil samples subjected to quantitative analysis. Concentrations ranged from 0.6 to 267.6 ng/g (carbazole); 0.2–7.2 ng/g (3-bromocarbazole); 0.0–9.1 ng/g (3-chlorocarbazole); 0.2–19.8 ng/g (3, 6-dibromocarbazole); 0.4–67.6 ng/g (3, 6-dichlorocarbazole); 0.0–0.7 ng/g (PCDDs); 0.0–0.3 ng/g (PCDFs) and 0.0–33.7 ng/g (PCBs). Concentrations decreased with depth and correlated positively to total organic carbon (TOC). When it was based on TOC%, an increase in concentration with depth was observed in most soil samples. With respect to dioxin-like toxicity, 3-bromocarbazole, 3-chlorocarbazole, 3, 6-dibromocarbazole and 3, 6-dichlorocarbazoles caused induction of CYP1A1-dependent EROD activity in HII4E rat hepatoma cell line. Their relative effect potency after 72 h exposure ranged from 0.00005 to 0.00013 and was directly related to the degree of halogenation with 2, 3, 7, 8-tetrachlorodibenzo-p-dioxin as reference. Furthermore, their contribution to overall soil dioxin-like toxicity was not significant in comparison to PCDD/Fs and PCBs though the sum toxic equivalency was limited to three halogenated carbazole congeners. Bromocarbazoles and chlorocarbazoles are emerging dioxin-like toxic environmental contaminants with potential for wide distribution occurring simultaneously with PCDD/Fs and PCBs. Graphical abstract: Highlights: Occurrence of bromocarbazoles and chlorocarbazoles in forest soils in Germany. The halogenated carbazoles occur simultaneously with PCDDs, PCDFs and PCBs. Bromocarbazoles are here reported for the first time in soil. Bromocarbazoles and chlorocarbazoles possess dioxin-like toxicity. Their relative effect potency is directly related to the degree of halogenation.